Interleukin‐10–mediated regenerative postnatal tissue repair is dependent on regulation of hyaluronan metabolism via fibroblast‐specific STAT3 signaling. Issue 3 (30th November 2016) - Balaji, Swathi; Wang, Xinyi; King, Alice; Le, Louis D.; Bhattacharya, Sukanta S.; Moles, Chad M.; Butte, Manish J.; de Jesus Perez, Vinicio A.; Liechty, Kenneth W.; Wight, Thomas N.; Crombleholme, Timothy M.; Bollyky, Paul L.; et al.
ABSTRACT: The cytokine IL‐10 has potent antifibrotic effects in models of adult fibrosis, but the mechanisms of action are unclear. Here, we report a novel finding that IL‐10 triggers a signal transducer and activator of transcription 3(STAT3)–dependent signaling pathway that regulates hyaluronan (HA) metabolism and drives adult fibroblasts to synthesize an HA‐rich pericellular matrix, which mimics the fetal regenerative wound healing phenotype with reduced fibrosis. By using cre‐lox‐mediated novel, inducible, fibroblast‐, keratinocyte‐, and wound‐specific STAT3‐knockdown postnatal mice—plus syngeneic fibroblast cell‐transplant models—we demonstrate that the regenerative effects of IL‐10 in postnatal wounds are dependent on HA synthesis and fibroblast‐specific STAT3‐dependent signaling. The importance of IL‐10‐induced HA synthesis for regenerative wound healing is demonstrated by inhibition of HA synthesis in a murine wound model by administering 4‐methylumbelliferone. Although IL‐10 and STAT3 signaling were intact, the antifibrotic repair phenotype that is induced by IL‐10 overexpression was abrogated in this model. Our data show a novel role for IL‐10 beyond its accepted immune‐regulatory mechanism. The opportunity for IL‐10 to regulate a fibroblast‐specific formation of a regenerative, HA‐rich wound extracellular matrix may lead to the development of innovative therapies to attenuate postnatal fibrosis in organ systems or diseases in which dysregulated inflammation and HA intersect.—Balaji, S., Wang, X., King, A., Le, L. D., Bhattacharya, S. S., Moles, C. M., Butte, M. J., de Jesus Perez, V.A., Liechty, K. W., Wight, T. N., Crombleholme, T. M., Bollyky, P. L., Keswani, S. G. Interleukin‐10‐mediated regenerative postnatal tissue repair is dependent on regulation of hyaluronan metabolism via fibroblast‐specific STAT3 signaling. FASEB J. 31, 868–881 (2017). www.fasebj.org